Financial technology inclusion in Islamic banks: implication on Shariah compliance assurance - Mohd Haridan, Nurfarahin; Sheikh Hassan, Ahmad Fahmi; Alahmadi, Hatem Abdulaziz (Human Resource Management Academic Research Society, 2020)
The global technology development has made rapid changes and revolution on the financial services landscape that enforce most banking system including Islamic banks to be more innovative and digitalized. In relation to the technology growth, Islamic banks are now collaborating with Financial Technology (FinTech) companies to grow their market shares. Through critical review of the literatures, we highlight that the inclusion of FinTech may provide important avenues for the Islamic banking industry to offer more innovative financial technology products while being conscious on the morality and Shariah compliant aspects. Besides the beneficial impact and value creation on the application of technology system and information, we also critically highlight several issues on financial risk associated from the technology development and Shariah compliance. We also highlight that it is crucial role for Shariah boards to have the necessary knowledge and skills and to be active with the management of Islamic banks in developing new financial technology products.